A molecular phylogeny of antarctic chironomidae and its implications for biogeographical history - ALLEGRUCCI, GIULIANA; CARCHINI, GIAN MARIA; SBORDONI, VALERIO; Todisco, V; Convey P (Springer, 2006)
The chironomid midges Belgica antarctica, Eretmoptera murphyi (subfamily Orthocladiinae) and Parochlus steinenii (subfamily Podonominae), are the only Diptera species currently found in Antarctica. The relationships between these species and a range of further taxa of Chironomidae were examined by sequencing domains 1 and 3–5 of 28S ribosomal RNA. The resulting molecular relationships between B. antarctica and E. murphyi, within Orthocladiinae, were highly supported by validation analyses, confirming their position within Chironomidae, as generated by classical taxonomy. Within Podonominae, P. steinenii from the Maritime Antarctic was more closely related to material from sub-Antarctic South Georgia than to material from Patagonia. Taking advantage of the availability of a molecular substitution rate calculated for this gene in Diptera, a dating of divergence between our study taxa was tentatively established. The divergence dates obtained were 49 million years (Myr), between B. antarctica and E. murphyi, and 68.5 Myr between these species and the closest Orthocladiinae taxon tested from Patagonia, suggesting that B. antarctica and E. murphyi were representatives of an ancient lineage. As both are endemic to their respective tectonic microplates, their contemporary distribution is, therefore, likely to have been shaped by vicariance rather than dispersal.